Trajectories and representations of Portuguese women overseas - Campos, Maria Christina Siqueira de Souza; Lunardelo, Paulo Henrique (Cadernos CERU, 2006)
Many academic studies have been written on Brazilian family, but more recently only a few of them focus on Portuguese family living abroad. This study analyses trajectories and representations of Portuguese women, who are living in four different countries as a consequence of migration due to various causes. There have been analyzed oral reports of women established in the USA as well as in Canada based on two studies worked out by other researchers that were compared to the reports collected especially for this study. The analysis showed that some traits are common to these women in the four countries, what is an important sign of the Portuguese culture force, but others reveal particularities that reflect the influence of the country where the immigrants remain and into it they are integrated.